Measuring procrastination at work and its associated workplace aspects. (October 2016) - Metin, U. Baran; Taris, Toon W.; Peeters, Maria C.W.
Abstract: Procrastination at work can be defined as putting off workrelated action by engaging in nonwork-related actions during work hours. This paper (a) introduces and validates a new instrument tapping procrastination behaviours at work, (b) investigates its construct validity (Study 1), and (c) presents empirical evidence on the workplace correlates of procrastination at work, including workplace characteristics, boredom and counterproductive work behaviour in two independent samples (Study 2). Drawing on data from 384 participants and using exploratory and confirmatory factor analysis, Study 1 revealed two subdimensions of the Procrastination at Work Scale (PAWS), namely soldiering and cyberslacking. Moreover, this study demonstrated that procrastination at work can empirically be distinguished from conceptually similar concepts such as counterproductive work behaviour, general procrastination and boredom. Study 2 further validated this instrument by examining its relations with other concepts. Structural equation analyses using data from participants from two culturally different countries (The Netherlands and Turkey, total N = 443) showed that low job demands and resources were associated with boredom and that boredom was associated with procrastination at work and counterproductive work behaviour. We conclude that the PAWS is a valid tool that can be used to assess non-work-related activity during work hours. Highlights: A generic scale for measuring procrastination at work was developed and validated. Distinction of work procrastination from other similar concepts was supported. An understimulating work environment was related to high levels of boredom. Procrastination at work was related to boredom and CWB. Differences across Dutch and Turkish samples were discussed.